The Importance of Teaching Listening Strategies in English Language Context - Fadila Latupono; Renata Nikijuluw (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2022)
Learning listening will assist us in improving another targeted skill considerably. People demand to hear several types of English repeatedly and continuously if they want to communicate appropriately, meaningfully, and naturally. The objective of this paper is to explore. The importance of listening strategies, The strategies in teaching listening, and listening processes, especially Bottom-up and top-down strategies. Another purpose of writing this paper is to show teachers how they can influence students' learning process—notably, using strategies to make it easier for students to learn listening.